New antifungal strategies and drug development against WHO critical priority fungal pathogens - Li, Yanjian; Liu, Yang; Jiang, Yicong; Yang, Yusen; Ni, Wanxing; Zhang, Wanli; Tan, Lingchen (Frontiers in Cellular and Infection Microbiology, 2025)
Fungal infections pose a significant threat to human health, particularly in immunocompromised individuals, driving a sustained increase in the demand for effective antifungal agents. These agents can be classified into several categories based on their mechanisms of action and chemical structures, including inhibitors of sterol synthesis, cell wall synthesis, DNA synthesis, and cell membrane function. Each class exerts its antifungal effects through distinct molecular pathways that disrupt fungal cell growth and reproduction. However, the clinical utility of current antifungal therapies is hindered by challenges such as the emergence of drug resistance, limited antifungal spectra, and adverse side effects. Consequently, the development of safe and efficacious antifungal agents remains a pressing need. This review provides a comprehensive overview of the classification and molecular mechanisms of antifungal drugs, discusses the current challenges in antifungal therapy, and explores potential strategies for future drug development, aiming to inform and advance antifungal research and treatment.